2023
DOI: 10.1111/irfi.12412
|View full text |Cite
|
Sign up to set email alerts
|

Environmental performance and employee welfare: Evidence from health benefit costs

Abstract: This article studies whether corporate environmental performance affects its health benefit costs. I find a firm's environmental performance is negatively associated with its employee health benefit costs. Cross‐sectional tests also show the effect is stronger for companies with improving employee health or located in a region with higher population health risks. In addition, the correlation only exists for chemicals released onsite as opposed to offsite release, indicating the effect is driven by the pricing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Research indicates that employee welfare is associated with job satisfaction, productivity, and corporate sustainability (Nusrat & Solaiman, 2016;Beloor, 2020;Alam et al, 2020). Prioritizing employee welfare is essential for talent retention and recruitment within organizations (Gu, 2023).…”
Section: Employee Wellbeing and Mental Healthmentioning
confidence: 99%
“…Research indicates that employee welfare is associated with job satisfaction, productivity, and corporate sustainability (Nusrat & Solaiman, 2016;Beloor, 2020;Alam et al, 2020). Prioritizing employee welfare is essential for talent retention and recruitment within organizations (Gu, 2023).…”
Section: Employee Wellbeing and Mental Healthmentioning
confidence: 99%
“…Moreover, firms seek to minimise the risks that are associated with employees by identifying environmental issues that present a challenge to the health and safety of employees (Chen et al, 2022;Geng et al, 2023;Han & Huo, 2020;Suharti & Sugiarto, 2020) and mitigate them to create a healthy working environment for them (Gouda & Saranga, 2020). Further, Li et al (2023) and Gu (2023) found that EP reduces health benefit costs by improving the employees' health. Based on the above discussion and also on the stakeholder's theory, we propose that EP will affect EHO.…”
Section: Ep and Ehomentioning
confidence: 99%